The Evaluation of Work Life Balance Strategies on the Performance of Female Entrepreneurial Businesses in Harare, Zimbabwe - Mawoyo, Aricia Pfungwa; Nani, Gwendoline Vusumuzi (Journal of Economics and Behavioral Studies, 2023)
The main purpose of the study was to investigate the effects of work-life balance (WLB) approaches on the productivity of female businesswomen in Harare, Zimbabwe. A positivist paradigm, a quantitative technique and a descriptive research design were utilized during the research. A sample of 100 randomly chosen female entrepreneurs was used to gather quantitative data utilizing electronic and self-administrated structured questionnaires. Classical Linear Regression analysis, Analysis of Variance (ANOVA), and Pearson’s correlation analysis were used to analyze the data. According to the study findings, female entrepreneurs in Harare integrated both work and home strategies to manage work-life balance. Employing competent and skilled workers, ranking tasks in terms of their priority levels, and scheduling work activities emerged as the highly effective work strategies from the study results. Correspondingly, the most effective home strategies involved hiring aids to lessen the workload, catering to urgent needs while at work and placing a higher priority on family pressing issues. The results also showed a positive correlation between home strategies and business performance as well as a substantial positive association between work strategies and business performance. The study concluded that integrating work and home techniques enabled female-owned businesses to operate better. The study suggested further research be done on the work-life balance of family-owned businesses, where both the wife and the husband were involved in the day-to-day running of the business, as well as that female entrepreneurs use the aforementioned strategies to improve their work-life balance and the performance of their businesses.